PERBANYAKAN ULIN (Eusideroxylon zwageri T.et.B) DENGAN BUI DAN SETEK - Utami, Ning Wikan; Hoesen, Djadja Siti Hazar; Witjaksono, Witjaksono; Danu, Danu (BERITA BIOLOGI, 2005)
The ulin or so called vernacular name kayu besi (Eusideroxylon zwageri T.et.B.) is one of the the important timber in East Kalimantan (East Borneo).However, there are some problems in the regeneration of this species. The research on propagation of ulin was carried out in Treub Laboratory, Research Center for Biology. The research consist of two experiments The research consisted of two experiments.The first experiment seeds which was treated in order to stimulate the germination and the second experiment by treating the mixture between 1BA and vitamin C for stimulating root cutting.The best result of seeds germination was recorded 90%,which the seeds were treated by removing the whole seedcoat and then by exposing to the sunlight for 5 hours The seed itself began to germinate 7 weeks after sowing.Meanwhile, the control no germination et all until 28 weeks.The best result on cutting was indicated by treating with the combination of IBA 10 mg/1 and vitamin C 50 mg/1 which was achieved the highest rooting 100%,although without hormone treatment only resulted 33.3% rooting.